Tourism Destination Competitiveness: Conceptual Analysis and Determinant Factors in a Literature Review - Siringoringo, Benny; Gultom, Rut Irmawati; Marbun, April; Pasaribu, Iwan R (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
Tourism destination competitiveness has become an important concept in understanding how destinations attract tourists, generate economic benefits, and sustain long-term tourism development in an increasingly competitive global tourism market. This study aims to analyze the conceptual framework and determinant factors influencing tourism destination competitiveness through a literature review approach. Relevant academic publications published between 2018 and 2023 were reviewed to identify key theoretical perspectives and empirical findings related to destination competitiveness. The results indicate that tourism destination competitiveness is a multidimensional construct influenced by several interrelated factors, including core tourism resources and attractions, infrastructure and accessibility, digital technology and innovation, and governance and policy frameworks. Natural and cultural attractions serve as the fundamental drivers that attract tourists, while infrastructure and accessibility facilitate mobility and improve visitor experiences. Furthermore, digital technologies play an increasingly important role in enhancing destination marketing, tourism services, and data-driven decision-making. Effective governance and collaborative stakeholder engagement are also essential for ensuring sustainable tourism development and long-term competitiveness. Overall, the findings highlight the importance of integrated strategies combining resource management, infrastructure development, technological innovation, and policy support to strengthen the competitiveness of tourism destinations.